Does green financial infrastructure promote the improvement and convergence of regional carbon emission efficiency? Based on provincial data of China - Zhang, Haijun; Wang, Jintao; Xu, Zhicang (Frontiers in Environmental Science, 2023)
The level of green financial infrastructure is measured using a symbiometric model with the Chinese provincial panel data from 2008 to 2020, and also the carbon emission efficiency is measured using the super-efficient SBM-DEA model with the carbon emission data at the provincial level. This paper tests the carbon emission efficiency improvement and convergence effects of green financial infrastructure using fixed-effects models, non-dynamic panel threshold models and spatial econometric models, while considering the role of environmental regulation in the process. It is found that green financial infrastructure significantly contributes to the improvement of carbon emission efficiency and accelerates the convergence rate of carbon emission efficiency between regions; the carbon emission efficiency improvement and convergence effects of green financial infrastructure are influenced by the intensity of environmental regulation, and we point out that either too strong or too weak environmental regulation will weaken the effectiveness of green financial infrastructure, which means there is a significant threshold effect; the spatial Durbin model (SDM) shows that the effect of green financial infrastructure on carbon emission efficiency has a spatial spillover effect of "neighbors as partners", that is, while green financial infrastructure promotes the improvement of carbon emission efficiency in the region, it also helps to promote the improvement of carbon emission efficiency in the neighboring regions. Therefore, China should accelerate the improvement of the green financial infrastructure system, improve the carbon emission rights market trading system, enhance the effectiveness of environmental regulation, and strengthen regional economic cooperation, so as to empower the development of low-carbon and green economic transformation.